PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM BERBASIS APLIKASI MICROSOFT EXCEL PADA CV. VISUAL MULTIMEDIA - Andreas Randy Wangarry; Raymond F. Rombot; Fanesa I. M. Syaefudin; Belthasar T. Siahaan (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
MSMEs in Manado City are still lacking in implementing SAK EMKM when preparing Financial Reports. This is due to a lack of understanding of the importance of making financial reports based on SAK. In addition to making it easier to read financial reports, it can also increase the transparency, effectiveness and efficiency of the financial reports that are made. One of the MSMEs that has not implemented financial reports based on this SAK is CV Visual Multimedia. This study aims to prepare financial reports based on SAK EMKM in CV. Visual Multimedia in Manado City. By conducting this research, it is hoped that it can provide useful information for MSMEs, the government, and financial institutions in increasing the effectiveness of SAK ETAP implementation for MSMEs, especially CV. Visual Multimedia in the management of Financial Statements refers to the Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). And also through this research can provide useful recommendations for the government, financial institutions, and MSMEs themselves in increasing the application of SAK ETAP in this city. This type of research in this study used qualitative research using the case study method. Data collection methods used are interviews, observation, documentation. Based on the results of the analysis it can be concluded that CV. During its establishment, Visual Multimedia has not implemented SAK EMKM in its accounting process. Accounting reporting is still done manually, namely recording on the book by the admin and then reporting it to the owner. These financial reports based on SAK EMKM based on Microsoft Excel will make it easier for admins to record transactions and generate financial reports. It also makes it easier for the owner to assess the performance of the business entity. Keywords: UMKM, Financial Statements, SAK EMKM, Microsoft Excel